GUIDELINES FOR ENHANCING THAI TEACHERS’ ARTIFICIAL INTELLIGENCE LITERACY IN THE DIGITAL AGE - Chakamanont, Sirin; Thabmali, Patcharaporn (Journal of Education and Innovation, 2025)
In the rapidly evolving digital age, Thai teachers must adapt to remain effective. This research aims to examine the level of artificial intelligence (AI) literacy among Thai teachers, analyze factors influencing their AI literacy, and develop guidelines to enhance this literacy. An explanatory sequential mixed-methods design was utilized, beginning with a quantitative survey of 584 Thai teachers to assess their AI literacy levels, followed by semi-structured interviews with 12 teachers selected from the initial sample for in-depth analysis of influencing factors. The findings from both quantitative and qualitative data were synthesized to draft AI literacy enhancement guidelines, which were then reviewed by experts to ensure quality and suitability. The study revealed that Thai teachers’ AI literacy level was moderate (M = 2.89, SD = 0.70). Teachers demonstrated an awareness of AI's benefits but lacked proficiency in practical application. Key factors affecting AI literacy included technological, personal, and environmental influences. The development of AI literacy enhancement guidelines encompasses three key areas including strategic actions for school administrators, practical measures for teachers, and curriculum and training design focusing on the ethical and safe use of AI. This research contributes to improving AI literacy among Thai educators and supports educational policymakers in crafting AI integration strategies, preparing teachers to adapt effectively to the evolving digital age. Additionally, promoting a clear understanding and responsible use of AI will create a strong foundation for Thailand's education system. This approach will empower Thai society to fully leverage AI technology, contributing to sustainable development across economic, social, and cultural dimensions.